Effect of bilirubin on toxicity induced by trifluoperazine, dibucaine and praziquantel to erythrocytes - Brito, MA (2015)
Unconjugated bilirubin (UCB), like trifluoperazine (TFP), dibucaine (DBC) and praziquantel (PZQ), induces erythrocyte morphological changes, lysis and lipid exfoliation. In the present study we determined whether TFP, DBC and PZQ toxicity to erythrocytes